2013
DOI: 10.3354/dao02628
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic identification of a nodavirus and a circular ssDNA virus in semi-purified viral nucleic acids from the hepatopancreas of healthy Farfantepenaeus duorarum shrimp

Abstract: Fisheries and aquaculture are impacted sporadically by newly emerged viral diseases. In most cases, searches for a causative pathogen only occur after a serious disease has emerged. As random shotgun sequencing (metagenomics) offers opportunities to identify novel viruses preemptively, the method was tested on nucleic acids extracted from the hepatopancreas of 12 healthy northern pink shrimp Farfantepenaeus duorarum captured from the Gulf of Mexico. Among the sequences, a nodavirus (Farfantepenaeus duorarum no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…It is also evident that CRESS DNA viruses are common in various marine organisms, as highlighted by recent discoveries in Acartia tonsa (marine copepod), Labidocera aestival (worms), Farfantepenaeus duorarum (shrimp) and A. crenata (gastropod) (Dayaram et al, 2013a,b;Dunlap et al, 2013;Ng et al, 2013). In addition, a diverse group of CRESS DNA viruses have also been identified in marine environments Labonte and Suttle, 2013;McDaniel et al, 2014;Yoon et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…It is also evident that CRESS DNA viruses are common in various marine organisms, as highlighted by recent discoveries in Acartia tonsa (marine copepod), Labidocera aestival (worms), Farfantepenaeus duorarum (shrimp) and A. crenata (gastropod) (Dayaram et al, 2013a,b;Dunlap et al, 2013;Ng et al, 2013). In addition, a diverse group of CRESS DNA viruses have also been identified in marine environments Labonte and Suttle, 2013;McDaniel et al, 2014;Yoon et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Other than Macrobrachium rosenbergii nodavirus (MrNV), and Penaeus vannamei nodavirus (PvNV) that have been reported previously, the covert mortality nodavirus (CMNV; Zhang et al, 2014) and Farfantepenaeous duorarum nodavirus (FdNV; Ng, Alavandi, Varsani, Burghart, & Breitbart, 2013) are the nodaviruses that have recently been identified to infect prawns. Although the viral infections are host species-specific, cross-species infection other than the native host has been observed in some nodaviruses: Red-spotted grouper nervous necrosis virus has been reported to infect Asian seabass, Lates calcarifer (Banerjee, Hamod, Suresh, & Karunasagar, 2014); Nile tilapia, Oreochromis niloticus (Keawcharoen et al, 2015); and Amphiprion sebae Bleeker, a marine clownfish (Binesh, Renuka, Malaichami, & Greeshma, 2013), whereas the MrNV has also been reported to infect Penaeus indicus, Penaeus monodon and P. vannamei (Ravi et al, 2009;Senapin et al, 2012).…”
Section: Nodavirusmentioning
confidence: 99%
“…Ng et al (2013) identified two nodaviruses from the pink shrimp ( Frafantepenaeus duorarum hepatopancreas ), which is a commercially important farmed shrimp species. One virus clone had a 403 nt insert encoding the RNA-dependent-RNA polymerase (RdRp) partial sequence while the other contained a 236 nt insert encoding a capsid protein partial sequence.…”
Section: Discovery Of New Viruses Using Viral Metagenomicsmentioning
confidence: 99%
“…Phylogenetic analysis showed that the capsid sequence was 43–51% similar to the shrimp nodaviruses, Macrobrachium rosenbergii nodavirus (MrNV) and P. vannamei nodavirus (PvNV), which causes white tail disease in prawns ( M. rosenbergii ), and muscle necrosis disease in shrimp ( Litopenaeus vannamei ) (Table 2). Apart from FdNV, Ng et al (2013) also identified the shrimp hepatopancreas associated circular virus (ShrimpCDV) from the digestive tract of the pink shrimp. Based on these findings, it can be concluded that viral metagenomics can be used to identify novel viral pathogens of shrimps.…”
Section: Discovery Of New Viruses Using Viral Metagenomicsmentioning
confidence: 99%
See 1 more Smart Citation